2021
DOI: 10.1108/ijsi-10-2021-0111
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in reliability analysis of aeroengine rotor system: a review

Abstract: PurposeTo provide valuable information for scholars to grasp the current situations, hotspots and future development trends of reliability analysis area.Design/methodology/approachIn this paper, recent researches on efficient reliability analysis and applications in complex engineering structures like aeroengine rotor systems are reviewd.FindingsThe recent reliability analysis advances of engineering application in aeroengine rotor system are highlighted, it is worth pointing out that the surrogate model metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 113 publications
(95 reference statements)
0
46
0
Order By: Relevance
“…However, the recently developed technique like surrogate modeling, hybrid MCS coupled with artificial intelligence, deep learning regression-based stratified probabilistic combined cycle fatigue damage evaluation is likely to obtain significantly accurate solutions to non-linear problems (Li et al. , 2022a, b, c). A detailed review of the recent advances in reliability analysis is provided in the literature (Li et al.…”
Section: Methodology For Reliability-based Design Of Tmsmentioning
confidence: 99%
“…However, the recently developed technique like surrogate modeling, hybrid MCS coupled with artificial intelligence, deep learning regression-based stratified probabilistic combined cycle fatigue damage evaluation is likely to obtain significantly accurate solutions to non-linear problems (Li et al. , 2022a, b, c). A detailed review of the recent advances in reliability analysis is provided in the literature (Li et al.…”
Section: Methodology For Reliability-based Design Of Tmsmentioning
confidence: 99%
“…, 2022; Hariri-Ardebili and Pourkamali-Anaraki, 2018; Keshtegar et al. , 2021), artificial neural network (ANN) (Li et al. , 2021; Cherid et al.…”
Section: Dynamic Reliability Analysis Of Single-objective Structurementioning
confidence: 99%
“…stress, deformation, strain and so forth) is determined by multiple dynamic deterministic analyses based on the material property, structure loads and dimensions, and the samples of input variables and output responses are obtained. Then the limit state function is approximated by the response surface method (RSM) (Lu et al, 2020;Zhang et al, 2017;Kaymaz and McMahon, 2005), support vector regression (SVM) (Feng et al, 2019;Chen et al, 2022;Hariri-Ardebili and Pourkamali-Anaraki, 2018;Keshtegar et al, 2021), artificial neural network (ANN) (Li et al, 2021;Cherid et al, 2021;Peng et al, 2019) and Kriging (Teng et al, 2022;Zhang et al, 2021a, b;Jiang et al, 2019a, b) surrogate model, and the reliability is analyzed by combining the allowable value. Zhang and Bai (2012) presented the extremum RSM used for the reliability analysis of a two-link flexible robot manipulator.…”
mentioning
confidence: 99%
“…There are many ways to classify uncertainties. For engineering problems, the most common classifications are aleatory uncertainty and epistemic uncertainty (Dantan et al, 2013;Shah et al, 2015;Li et al, 2021;Yang et al, 2022), which is shown in Figure 2. Aleatory uncertainties exist objectively and cannot be reduced.…”
Section: Introductionmentioning
confidence: 99%